"La leve sancion en delito de estupro,propuesta: reforma el articulo 510 del codigo penal" - Espinel Avilés, Agustín Orlando (2011)
In this legal research project I have covered fundamental aspects in order to determine that the Penal Code on Sex Crimes needs to be reformed with drastic penalties according to the crime committed. For the best understanding of this legal research project I have developed it in the following way: In the first chapter I started by addressing the historical background in the matter of statutory crime in order to analyze the way in which said criminal act was sanctioned in the old legislations, based on Roman Law; as well as in the middle ages also in the Spanish and Latin American times, times in which they agree that in this crime the goal of rape was reached by deception, flattery and even force. In the second chapter make an analysis of rape as a sexual crime understanding the situation of the taxpayer and the elements that make up the crime of rape since this crime is a way out of the crime of rape, and therefore should be imposed a more drastic penalty . In the third chapter I have used the different research methods, making a general study, analyzing the facts and phenomena particular to the crime of rape, which allowed to establish conclusions and the real events that occur around this type of crime. In the fourth chapter I have been able to perceive that the issue of sexual abuse in minors is not treated in depth, even though we are talking about minors, but how many will not be denounced due to the threats of the active subject to their children. victims, since justice remains motionless if there is no complaint in between. In the fifth chapter I have made the respective conclusions and recommendations of the present investigative project according to the interviews carried out with the Prosecutor of minors, Judges of criminal guarantees, legal professionals and especially the community. In the sixth chapter I conclude with the proposal that is to reform article 510 of the Penal Code, regarding the established punishment since it is very light and in turn for being a crime of imprisonment is susceptible bail and we know that we are facing a part vulnerable of our